2011
DOI: 10.1002/anie.201107495
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Diastereo‐ and Enantioselective Reaction for Constructing Functionalized Cyclohexanes: Six Contiguous Stereocenters in One Step

Abstract: Organic motifs with contiguous multiple stereocenters exist in numerous natural and unnatural products that exhibit important biological activity.[1] The number of possible stereoisomers increases exponentially with the number of stereocenters, thus the highly stereoselective synthesis of chiral compounds with multiple stereocenters from simple starting materials is a challenge. Nature has developed many efficient ways to construct such structures from simple starting materials, as demonstrated by the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…Along with others, we have noted that reactions involving transition-metal enolates display enhanced rates in alcoholic solvent. 6h,21 In fact, the use of i PrOH gave a >20:1 preference for the desired product 3a (Table 1, entry 11: 77% yield, 70% ee, 11:1 dr). The protic solvent may promote fragmentation of less-active catalyst oligomers, 22 or catalyst turnover from the Cu(II)-alkoxide intermediate proceeding [3 + 2]-cycloaddition via protonolysis.…”
Section: Resultsmentioning
confidence: 95%
“…Along with others, we have noted that reactions involving transition-metal enolates display enhanced rates in alcoholic solvent. 6h,21 In fact, the use of i PrOH gave a >20:1 preference for the desired product 3a (Table 1, entry 11: 77% yield, 70% ee, 11:1 dr). The protic solvent may promote fragmentation of less-active catalyst oligomers, 22 or catalyst turnover from the Cu(II)-alkoxide intermediate proceeding [3 + 2]-cycloaddition via protonolysis.…”
Section: Resultsmentioning
confidence: 95%
“…In the same vein, two years later, Huang and co‐workers demonstrated that 1,2‐ketoesters could efficiently participate in an closely related domino pseudo‐three‐component enantioselective Michael/Michael/Henry sequence with nitroalkenes as electrophiles catalyzed by a new copper(II) complex incorporating a rigid chiral diamine (Scheme ) 54. The acetate counter anion was found to be crucial for good reactivity and high stereoselectivities.…”
Section: Mbfts With Three Bond‐forming Eventsmentioning
confidence: 97%
“…For instance, organocatalyzed aldol reactions of enamines derived from α‐keto acids with aldehydes, followed by esterification of the carboxylic group with the resulting carbinol gave access to highly substituted furan‐2( 5H )‐ones (Scheme ) . Domino sequences involving conjugate addition of α‐keto esters with nitroalkenes have been also described to synthesize highly substituted cyclohexane units stereoselectively (Scheme ) . Moreover, α‐keto carboxylic acid derivatives can undergo decarboxylative reactions, generating a valuable acyl anion intermediate, through the extrusion of CO 2 .…”
Section: Introductionmentioning
confidence: 99%